Computer security -- ESORICS 2016. 21st European Symposium on Research in Computer Security, Heraklion, Greece, September 26-30, 2016, proceedings /: 21st European Symposium on Research in Computer Security, Heraklion, Greece, September 26-30, 2016, proceedings. Part II : (2016) - Unknown
No abstract available